“Os dois vizinhos. Cenas da colônia”, de Wilhelm Rotermund - Neumann, Gerson (Contingentia, 2009)
The story “Os dois vizinhos. Cenas da Colônia” (Die beiden Nachbarn. Bilder aus der Kolonie), written by Wilhelm Rotermund, was published in 1883 and 1884 in two parts in the Kalender für die Deutschen in Brasilien. The text by Rothermund represents many relevant aspects of the immigration of German Lutherans to Brazil. This article will first give an overview on the work of Wilhelm Rotermund and than offer a critical analysis of Die beiden Nachbarn. Bilder aus der Kolonie. A third point of interest will be the importance of preserving the mother language (German) and the rural-urban relationship.